2007
DOI: 10.1128/aac.01447-06
|View full text |Cite
|
Sign up to set email alerts
|

Selective Phosphorylation of Antiviral Drugs by Vaccinia Virus Thymidine Kinase

Abstract: The antiviral activity of a new series of thymidine analogs was determined against vaccinia virus (VV), cowpox virus (CV), herpes simplex virus, and varicella-zoster virus. Several compounds were identified that had good activity against each of the viruses, including a set of novel 5-substituted deoxyuridine analogs. To investigate the possibility that these drugs might be phosphorylated preferentially by the viral thymidine kinase (TK) homologs, the antiviral activities of these compounds were also assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 54 publications
(57 reference statements)
5
34
0
Order By: Relevance
“…CldU [8]. The phosphorylation studies we conducted using vaccinia-virus-infected cells treated with thymidine, BrdU and IdU confirmed that higher levels of nucleoside triphosphate were produced in TK + virus-infected LLC-MK 2 cells.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…CldU [8]. The phosphorylation studies we conducted using vaccinia-virus-infected cells treated with thymidine, BrdU and IdU confirmed that higher levels of nucleoside triphosphate were produced in TK + virus-infected LLC-MK 2 cells.…”
Section: Discussionmentioning
confidence: 81%
“…In the cell lines used in the research, viral TK made an additional contribution toward enhancing phosphorylation and increasing antiviral potency of the 2′-deoxyuridines. Other investigators have indicated that poxvirus TK is responsible for activation (monophosphorylation) of certain nucleoside analogues related to thymidine [7,8]. Some of those compounds were highly dependent upon viral TK for antiviral activity, suggesting that phosphorylation by cell TK was minimally contributory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HSV isolates were evaluated in a blinded fashion (University of Alabama, Birmingham, AL, USA) for potential resistance to penciclovir, the active metabolite of famciclovir, by plaque reduction assays 13 . An isolate was considered sensitive to penciclovir if the 50% effective concentration (EC50) value was <5 mg/mL.…”
Section: Methodsmentioning
confidence: 99%